2019
DOI: 10.1016/j.cell.2019.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2

Abstract: Highlights d Orthogonal DNA sequencing approaches are required to observe all variant types d De novo SNVs and indels accompany non-recurrent structural variants (SVs) in cis d SV-associated SNVs primarily occur within genes and over megabase-sized distances d MMBIR involves extensive DNA replication resulting in regional hypermutation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 82 publications
0
72
0
Order By: Relevance
“…The result of our study has shown that there were no significant homologies between proximal and distal breakpoints, and microhomologies were frequently observed at the duplication junctions, along with sequence insertions. The presence of microhomology at the junctions and their position within stem‐loop structures support the concept that SNCA duplication arose from stalled replication forks, which then restarted at ectopic sites upon minimal pairing with an acceptor template, as described by the FoSTeS/MMBIR models of replication repair . Template switching may be reiterative, as suggested by case 5, where the microinsertion may have been acquired from either chromosome 6 or 21, and case 4, in which the ATTTGTCAA motif was copied twice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The result of our study has shown that there were no significant homologies between proximal and distal breakpoints, and microhomologies were frequently observed at the duplication junctions, along with sequence insertions. The presence of microhomology at the junctions and their position within stem‐loop structures support the concept that SNCA duplication arose from stalled replication forks, which then restarted at ectopic sites upon minimal pairing with an acceptor template, as described by the FoSTeS/MMBIR models of replication repair . Template switching may be reiterative, as suggested by case 5, where the microinsertion may have been acquired from either chromosome 6 or 21, and case 4, in which the ATTTGTCAA motif was copied twice.…”
Section: Discussionmentioning
confidence: 57%
“…Local rates of hypermutation and DNA structural features have been shown to predispose to nonrecurrent structural variations . A map of common SNPs along chromosome 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleotide identity of 100% between the proximal and distal reference strands leading to the junction was considered microhomology when found in a subtractive state in the patient's DNA sequence (i.e., identical sequence found once only in the patient's DNA at the deletion junction; Carvalho & Lupski, ). Microhomeology was defined as imperfect matches leading to the junction (cutoff of 70% identity with a maximum two‐nucleotide gap followed by at least two perfectly matched nucleotides; adapted from Beck et al, ; Liu et al, ). Microhomeology at the breakpoint‐junctions was recently reported as a feature associated with the replication‐based mechanism of SV formation (Bahrambeigi et al, ; Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…62,63 Microhomology has been reported as a signature for a class of DNA replication errors that can generate CNVs (see Discussion). 64,65 As a positive control for our aCGH analysis, we also included a known SNCA triplication sample from the index family in which SNCA locus multiplication was first discovered as a cause for PD. [38][39][40][41] Breakpoint sequencing revealed that this copy number alteration is a 1.7 Mb complex genomic rearrangement ( Figure 1B), consisting of a duplication-inverted triplication-duplication (DUP-TRP/INV-DUP).…”
Section: Copy Number Variantsmentioning
confidence: 99%